Highly stable and Pb-free bismuth-based perovskites for photodetector applications. (24th June 2020) - Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Aher, Rahul; Punde, Ashvini; Waghmare, Ashish; Shinde, Pratibha; Vairale, Priti; Waykar, Ravindra; Doiphode, Vidya; Jadkar, Vijaya; et al.
Abstract : Herein, we report synthesis of highly stable, Pb-free bismuth iodide, stoichiometric methylammonium bismuth iodide and non-stoichiometric methylammonium bismuth iodide perovskite thin films for photodetector applications. Abstract : Herein, we report the synthesis of highly stable, Pb-free bismuth iodide (BiI3 or BI), stoichiometric methylammonium bismuth iodide [(CH3 NH3 )3 Bi2 I9 or MA3 Bi2 I9 or s-MBI] and non-stoichiometric methylammonium bismuth iodide [(CH3 NH3 )2 BiI5 or MA2 BiI5 or Ns-MBI] perovskite thin films for photodetector applications. These films are synthesized at room temperature by a single step solution process spin coating method. The structural, optical, and morphological properties of these films were investigated using different characterization techniques such as XRD, Raman spectroscopy, FE-SEM, UV-Visible spectroscopy, etc. Formation of BI, s-MBI and Ns-MBI thin films is confirmed by XRD and Raman spectroscopy measurements. XRD analysis reveals that BI has a hexagonal crystal structure and a P 63 / mmc hexagonal space group for s-MBI and Ns-MBI. The optical properties of BI thin films show a high absorption coefficient (∼10 4 cm −1 ) and a band gap of ∼1.74 eV. Similarly, s-MBI films have a high absorption coefficient (∼10 3 cm −1 ) and an indirect band gap of ∼1.8 eV. Moving from s-MBI to Ns-MBI, the value of absorption coefficient is ∼10 3 cm −1 and the band gap corresponds to ∼2 eV. Finally, photodetectors based on the synthesized BI, s-MBI and Ns-MBI perovskites have been directly fabricated on FTO substrates. All photodetectors exhibited highly stable photo-switching behaviour along with excellent photoresponsivity and detectivity, with a fast response and recovery time. Our work demonstrates that Pb-free BI, s-MBI and Ns-MBI perovskites have great potential in the future for realizing stable photodetectors.